Dioscin Alleviates Cardiac Dysfunction in Acute Myocardial Infarction via Rescuing Mitochondrial Malfunction - Shen, Tianyu; Lyu, Dayin; Zhang, Mengping; Shang, Hui; Lu, Qiulun (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction is one of the most severe heart diseases, leading to sudden death. Currently, angiography and stenting are widely performed in clinics, yet more effective treatment is still needed. Herein, we presented that dioscin, a natural product, showed protective effect on infarcted hearts via mitochondrial maintenance. Upon dioscin treatment, cardiac dysfunction was alleviated, and remodeling is prevented. Mechanistically, disocin maintains mitochondria function through the maintenance of Kreb's cycle, and suppresion of ROS accumulation. In this way, by targeting mitochondrial dysfunction, dioscin is a potential drug for infarcted hearts.